An insight into the diagnostic and prognostic value of HOX A13's expression in non‐muscle invasive bladder cancer. Issue 9 (19th July 2022) - Setti Boubaker, Nouha; Gurtner, Aymone; Trabelsi, Nesrine; Manni, Isabella; Blel, Ahlem; Saadi, Ahmed; Chakroun, Marouene; Naimi, Zeineb; Zaghbib, Selim; Ksontini, Meriam; Meddeb, Khedija; Rammeh, Soumaya; et al.
Abstract: Background: Several studies have interrogated the molecular pathways and their interacting genes underlying bladder cancer (BCa) tumorigenesis, yet, the role of homeobox genes is still poorly understood. Specifically, HOXA13, which plays an important role as a major actor in the urogenital tract's development. Methods: Immunohistochemical (IHC) staining was performed to inspect the differential expression of HOXA13 protein in non‐muscle‐invasive bladder cancer (NMIBC) and non‐tumoral tissues. A semiquantitative scoring system was adopted to evaluate the IHC labeling. Correlation to clinical parameters was performed by descriptive statistics. Overall survival was estimated by the Kaplan–Meier method and Cox regression model. The functional HOX A13 protein association networks (PPI) were obtained using String 11.0 database. Results: HOX A13 exhibited cytoplasmic and nuclear staining. Its expression levels were lower in high‐grade NMIBC (HG NMIBC) compared to low‐grade ones (LG NMIBC). The expression of HOX A13 was correlated to tumor grade (LG/HG) ( p  = 0.036) and stage (TA/T1) ( p  = 0.036). Nevertheless, its expression was not correlated to clinical parameters and was not able to predict the overall survival of patients with HG NMIBC. Finally, PPI analysis revealed that HOX A13 seems to be a part of a molecular network holding mainly PBX1, MEIS, ALDH1A2, HOX A10, and HOX A11. Conclusion: The deregulation of HOX A13 is not associated with the prognosis of BCa. It seems to be rather implicated in the early initiation of urothelial tumorigenesis and thus may serve as a diagnostic marker in patients with NMIBC. Further experimentations on larger validation sets are mandatory. Abstract : HOXA13 is a major actor of the urogenital tract's development. Yet, its role in BCa tumor initiation, diagnosis and prognosis is still not well known. Our data revealed that HOX A13is implicated in the early initiation of urothelial tumorigenesis but is not associated to prognosis. Thus, it may serve as a diagnostic marker for patients with NMIBC.